Traditional Knowledge in a Rural Community in the Semi-Arid Region of Brazil: Age and gender patterns and their implications for plant conservation - Arévalo-Marín, Edna; Lima, José Ribamar de Farias; Palma, Alexandre Ramlo Torre; Lucena, Reinaldo Farias Paiva de; Cruz, Denise Dias da (Ethnobotany Research and Applications, 2015)
The present study documents dynamics and patterns of knowledge about the use of native plants in a rural community, according to the age and gender of its members, in a semi-arid region of Paraíba State, northeastern Brazil. Socioeconomic factors and ethnobotanical data were registered from 123 household heads through semi-structured interviews. Comparisons between the knowledge of males and females, and between age groups about species richness, number of citations mentioned, and species plant use knowledge measures were made to determine intracultural variations. These outcomes show that differentiation of botanical knowledge from a gender and age perspective reinforces the importance of recognizing specific activities and needs in males and females in the design and definition of sustainable management strategies, policies, and economic interventions over vegetation legacy, and act as a priority inclusion indicator of certain species in conservation processes as a contribution to the culture and biodiversity conservation.